2019
DOI: 10.1021/acs.iecr.9b01459
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Activity and Selectivity of H2O2 Formation from H2 and O2 over Au-Based Catalysts

Abstract: Fundamental understanding of the structure sensitivity of Au-catalyzed H 2 O 2 formation from H 2 with O 2 is of prime scientific and industrial significance. Herein, DFT calculations are employed to reveal the underling nature of the site-dependent H 2 O 2 formation activity and selectivity over three typical Au(111), Au(100), and Au(211) sites. The hydrogen dissociation is suggested as the ratedetermining step. The structural and charge analysis and the energy barrier decomposition indicate one lower-coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Notably, the Au 4f spectra were deconvoluted using a non‐linear least squares algorithm with a Shirley base line and a Gaussian–Lorentzian combination, and the Au 4f spectra of the two catalysts both clearly show that the intensity ratio of Au 4f 5/2 and Au 4f 7/2 is 3/4 with a splitting of 3.7 eV, which are well consistent with the characteristic of Au 0 species . According to previous theoretical studies, the hydrogen dissociation is suggested as rate‐determining step in the hydroperoxy species generation on the Au catalysts, and the higher Au binding energy is favorable for the increased Au‐H interaction and thus the hydrogen dissociation. These analyses would explain why under the reaction of 18 hr, the Au/TS‐2‐B catalyst exhibits higher stable PO formation rate and hydrogen efficiency than the Au/TS‐1‐B catalyst.…”
Section: Resultssupporting
confidence: 66%
“…Notably, the Au 4f spectra were deconvoluted using a non‐linear least squares algorithm with a Shirley base line and a Gaussian–Lorentzian combination, and the Au 4f spectra of the two catalysts both clearly show that the intensity ratio of Au 4f 5/2 and Au 4f 7/2 is 3/4 with a splitting of 3.7 eV, which are well consistent with the characteristic of Au 0 species . According to previous theoretical studies, the hydrogen dissociation is suggested as rate‐determining step in the hydroperoxy species generation on the Au catalysts, and the higher Au binding energy is favorable for the increased Au‐H interaction and thus the hydrogen dissociation. These analyses would explain why under the reaction of 18 hr, the Au/TS‐2‐B catalyst exhibits higher stable PO formation rate and hydrogen efficiency than the Au/TS‐1‐B catalyst.…”
Section: Resultssupporting
confidence: 66%
“…The coverage-dependent model indicates that the formation of H 2 O 2 is not through OH* + OH* → H 2 O 2 + * + *, leading to a lower rate for this elementary step compared with that found for OOH* + H* → H 2 O 2 + * + *. The readsorption of H 2 O 2 on low-coordinated terrace and edge sites shows a facial dissociation through H 2 O 2 + * + * → OH* + OH*. , The dissociation of H 2 O 2 to two OH surface species is another important channel for the water formation. ,,,,,, We find that there are two reasons why the reaction pathways through O 2 + * → O 2 *, O 2 * + H* → OOH* + *, and OOH* + H* → H 2 O 2 + * + * dominate on Pd(111) with the coverage effects. The reasons are as follows.…”
Section: Resultsmentioning
confidence: 80%
“…The direct O 2 dissociation is facile compared with O 2 hydrogenation, followed by the hydrogenation of O surface atoms. The 33,103 The dissociation of H 2 O 2 to two OH surface species is another important channel for the water formation. 1,9,23,27,28,86,104 We find that there are two reasons why the reaction pathways through .05 eV if the coverage effect is included, which can be seen in the energy profiles (Figure S19).…”
Section: Resultsmentioning
confidence: 99%
“…). To further increase the activity of Ru-based catalysts, recent advances are focused on the construction of electron-rich Ru nanoparticles (NPs) on nanostructured supports (like hierarchical porous carbon and layered double hydroxides) or by choice of a specific support (reduced graphene oxide, nitrogen-doped carbon, etc. ). This is because electron-rich Ru NPs can facilitate the CO activation and thus improve the hydrogenation activity. However, only surface electron-rich Ru species can be available for these Ru NP catalysts, and they cannot activate CO and boost H 2 dissociation simultaneously, though H 2 dissociation is crucial for hydrogenation reactions. It has been demonstrated that electron-rich Ru could promote H 2 dissociation and thereby enhance the CO 2 hydrogenation activity, and this is also confirmed by atomically dispersed Ru catalysts that enhance the Fischer–Tropsch synthesis . Inspired by these pioneering investigations, it is promising to develop electron-rich Ru species at the atomic scale and is expected to facilitate H 2 dissociation as well and further improve their activity toward LA hydrogenation.…”
Section: Introductionmentioning
confidence: 99%